First record of the genus Sceloattalus Wittmer, 1966 (Coleoptera, Malachiidae) from China, with description of a new species - Tong, Junbo; Tshernyshev, Sergei E.; Liu, Haoyu; Yang, Yuxia (ZooKeys)
The genus Sceloattalus Wittmer, 1966 is recorded from China for the first time. A new species, S. nigroprominens Tong & Yang, sp. nov., is described and illustrated from Xizang Autonomous Region of China. This new species is the fourth member of Sceloattalus and can be easily distinguished from others by the yellow antennae with a small black spot at apex of last antennomere, black elytra without metallic lustre, all tarsi yellow, and hind tibiae yellow to black. The generic diagnosis of Sceloattalus is resummarized. An identification key to all known species of Sceloattalus is also updated.